PENGARUH BRAND IMAGE, BRAND TRUST, BRAND AWARENESS DAN PRODUCT QUALITY TERHADAP BRAND LOYALTY SARI ROTI (Studi Pada Konsumen Sari Roti Mahasiswa Universitas Islam Malang) - Desi Ristanti; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to examine and analyze the influence of brand image, brand trust, brand awareness and product quality on Sari Roti brand loyalty both partially and jointly. The population and samples are consumers of Sari Roti Malang Islamic University Students totaling 99 people. Data collection through questionnaires. Data analysis in this study used SPSS version 16. The sampling technique in this study used purposive sampling technique and data testing techniques used in this study include validity test, reliability test, classic assumption test, multiple linear regression analysis, hypothesis testing and coefficient research determination.The results of the analysis show that (1) the brand image variable is tested partially by using the t test to produce a value of t count of 0.386 <t table 1,985 and a significance value of 0.700> the significance rate is 0.05. Based on these results indicate that the brand image variable has no significant positive effect on brand loyalty. (2) the brand trust variable is tested partially by using the t test to produce a value of t count equal to 3.038> t table 1.985 and a significance value of 0.003 <significance level that is 0.05. Based on these results indicate that the brand trust variable has a positive and significant effect on brand loyalty. (3) the brand awareness variable was tested partially by using the t test resulting in the value of t arithmetic of 1.818 <t table of 1985 and the significance value of 0.068> the significance rate of 0.05. Based on these results indicate that variable brand awareness has a positive and not significant effect on brand loyalty. (4) the product quality variable is tested partially by using the t test to produce a value of t count of 3.792> t table in 1985 and a significance value of 0.000 <the significance rate of 0.05. Based on these results indicate that product quality variables significantly influence brand loyalty. (5)Keywords: Brand Image, Brand Trust, Brand Awareness, Product Quality and Brand Loyalty.